Respuesta :

Answer:

the slant asymptote is

y = x - 2

Step-by-step explanation:

First divide the denominator into the numerator.

Then the slant asymptote is

y

=

x

2

Answer:

[tex]f(x)=x+2[/tex]

Step-by-step explanation:

The slant/oblique asymptote of a rational function is equal to its quotient without the remainder

Use synthetic division:

1 | 1  1   4

___ 1   2

   1 2 | 6

Therefore, the slant asymptote of [tex]f(x)=\frac{x^2+x+4}{x-1}[/tex] is [tex]f(x)=x+2[/tex].

Ver imagen goddessboi
ACCESS MORE